Types of Expressive Illocutionary Acts Found in the Movie “True Spirit” by Sarah Spillane - Mete, Novita Serianna; Winarta, Ida Bagus Gde Nova (Jurnal Penelitian Mahasiswa Indonesia, 2024)
This study was aimed to analyze the types of expressive illocutionary acts found in the movie “True Spirit" by Sarah Spillane. An expressive illocutionary act is a type of expression such as Thanking, Apologizing, Attitude, Greeting, Wishing, and Congratulating. To analyses the data, there are several data collection techniques performed by the researcher, such as; downloading movies, watching movies, and taking notes what some of the characters say. In addition, to classifying data included in expressive illocutionary acts. This study uses a qualitative descriptive method which includes expressions in the form of words or sentences in the form of expressive illocutionary acts in the movie. In this study, the types of expressive illocutionary acts used theory proposed by Searle (1979) to determine expressive illocutionary acts in conversation in the movie “True Spirit”. Based on the data, there are 27 utterances found in the movie. As the result of the analysis there are 6 types of Expressive illocutionary act found in the “True Spirit” movie. There are thanking, apologizing, greeting, attitude, wishing, and also congratulating. The types of Thanking consist of 7 utterances, apologizing consist of 5 utterances, greeting consist of 5 utterances, attitude consist of 5 utterances, wishing consist of 3 utterances and also the last is congratulating consist of 2 utterances.